Mergers & acquisitions and partnerships in China - Coispeau, Olivier (World Scientific, 2015)
This book provides an in-depth analysis of mergers, acquisitions, and strategic partnerships in the business world. It explores the financial, managerial, and legal aspects of corporate restructuring, with a particular focus on strategies for growth, value creation, and integration. Through real-world examples and case studies, the author offers practical insights into how companies can achieve successful partnerships and sustainable competitive advantage.